PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN LINGKUNGAN SEBAGAI SUMBER BELAJAR DI KELAS III - Suneti, Suneti; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve students' skill in writing descriptions by utilizing environmental media as a learning resource.This research uses descriptive method with form of action research class (PTK) and it is a collaborative research. Subjects in this study were teachers as researchers and students of class III A which is amounted to 32 students. Technique used in this research is observation and study of document and to collect the data, researcher used observation sheet and document study sheet. Based on the results of the research that has been done, it showed that the skill of writing the essay description of students in the first cycle was seen from 32 students who could pass it were 40.63% (13 students) while students who did not pass it were 59.37% (19 students) with the average score of 70, 74. Experienced improvement in cycle II of 32 students who could pass it were 62,5% (20 students) while students who did not pass it were 37,5% (12 student) with average score 73,43.In this study, the student learning outcomes increased cycle of 70.74. In the second cycle, the average increased to 73.43. From the data obtained shows that using the environmental media as a learning resource can improve the skills of writing essay students in class III A State Elementary School 20 South Pontianak.Keywords: Descriptionessay, Surrounding environmental media